Socio-Economic Determinants of Residential Satisfaction in Eldoret Municipality, Kenya - Alima, D.T.; Kiplagat, A.; Mwasi, B. (Africa Environmental Review Journal, 2021)
The concept of residential satisfaction is directly linked to the planning discipline such that the appeal to comply with planning standards is aimed at ensuring that housing developments are safe and habitable. Planning sets up standards and regulations to guide the development of essential attributes of residential areas whereas residential satisfaction is a subjective response to the same, that is dwelling unit and neighbourhood attributes of housing. Household socio-economic characteristics influence the need for and access to housing of desired quality, which in turn affect residential satisfaction. This is expected because people who build or purchase homes use a checklist of needs to settle for the desired housing unit. Even so, research in residential satisfaction is limited. As a result, housing developments have been made based on the expertise of planners and policy makers with little to no consideration for the aspirations of the people. This study sought to determine how socio-economic characteristics impact on residential satisfaction for them to be infused in residential area planning and development. Data for the study was sought from three residential neighbourhoods in Eldoret Municipality. Ordinal Logistic Regression (OLR) was used to model the relationship. Age, marital status, employment, income and house tenure were significant determinants of residential satisfaction while household size and level of education were non-significant determinants of residential satisfaction. The study concluded that socioeconomic attributes of a household impact on residential satisfaction. It therefore recommended that in order to improve satisfaction in housing development, socioeconomic characteristics of the people must be emphasized as they reflect the diversity of housing needs.